A Simple Monitoring Network System of Wireless Sensor Network - Shengjun Su; Shuozhong Wang (Institute of Advanced Engineering and Science, 2012)
A SSNS (simple sensor network sniffer) is used to analyze and evaluate the Wireless Sensor Networks (WSN) effectively. SSNS is designed to monitor IEEE 802.15.4 protocol frame, which based on the Ethernet. Unlike the existed monitoring system, our design is much simpler and needs less resource. It is analyzed in this paper that the monitor network framework, time synchronization, and analysis program design. The results show that SSNS works stably, and can real-time display the frame monitored and reflect the dynamic change of WSN.